Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied physics. B, Lasers and optics, 2016)
The term quantum physics refers to the phenomena and characteristics of atomic and subatomic systems which cannot be explained by classical physics. Quantum physics has had a long tradition in Germany, going back nearly 100 years. Quantum physics is the foundation of many modern technologies. The first generation of quantum technology provides the basis for key areas such as semiconductor and laser technology. The “new” quantum technology, based on influencing individual quantum systems, has been the subject of research for about the last 20 years. Quantum technology has great economic potential due to its extensive research programs conducted in specialized quantum technology centres throughout the world. To be a viable and active participant in the economic potential of this field, the research infrastructure in Germany should be improved to facilitate more investigations in quantum technology research.